2020
DOI: 10.1177/1120672120941433
|View full text |Cite
|
Sign up to set email alerts
|

Orbital anatomical parameters affecting outcome of deep lateral orbital wall decompression

Abstract: Purpose: To determine orbital anatomical parameters that affect surgical outcome of deep lateral orbital wall decompression. Methods: Twenty orbits of 20 patients with moderate proptosis (maximum 25 mm) due to thyroid eye disease who were stable for at least 6 months were included in this prospective cohort study. Four parameters including lateral orbital wall distance (LOWD), removable surface area (RSA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
(59 reference statements)
1
5
0
1
Order By: Relevance
“…This was stressed by Shin et al [43] who investigated safe zones for decompression surgery in the lateral orbit in non-EO CT-scans, although their data on the sphenoid trigone cannot be compared with our findings due to different measurements. Furthermore, an analysis of anatomical parameters affecting the outcome of decompression surgery in EO showed that sphenoid trigone removal was an independent important factor [44]. Comparing EO to non-EO data, a statistically significant difference regarding the sphenoid trigone was seen in our study highlighting the importance of this structure.…”
Section: Plos Onesupporting
confidence: 47%
See 1 more Smart Citation
“…This was stressed by Shin et al [43] who investigated safe zones for decompression surgery in the lateral orbit in non-EO CT-scans, although their data on the sphenoid trigone cannot be compared with our findings due to different measurements. Furthermore, an analysis of anatomical parameters affecting the outcome of decompression surgery in EO showed that sphenoid trigone removal was an independent important factor [44]. Comparing EO to non-EO data, a statistically significant difference regarding the sphenoid trigone was seen in our study highlighting the importance of this structure.…”
Section: Plos Onesupporting
confidence: 47%
“…As Borumandi et al pointed out in a review paper, sound anatomical knowledge is a prerequisite for surgical success in EO decompression surgery [91], and this study furnishes new anatomical data. The sphenoid trigone and its anterior-posterior dimensions seem to be of special importance as surgical parameters in decompression surgery discussed in Cruz et al 2021 [92] and described as an important surgical factor by Rajabi et al [44]. Furthermore, the data provided on orbital rim anatomy, especially supraorbital rim protrusion and lateral rim retrusion can be important in planning EO decompression surgery [15].…”
Section: Plos Onementioning
confidence: 99%
“…48 Alacrima has also been reported infrequently with superolateral orbital ab interno dissection. 49…”
Section: Complicationsmentioning
confidence: 99%
“…Extensive removal of the bony wall overriding the temporalis muscle can result in oscillopsia. 49–51…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation